Christianity, Book-Burning and Censorship in Late Antiquity. Studies in Text Transmission - Rohmann, Dirk (Arbeiten zur Kirchengeschichte, 2016)
The role of Christian institutions, writers and saints in the active suppression and destruction of books in Late Antiquity has received surprisingly little consideration. The author argues that texts and ideas from materialistic philosophical traditions were vulnerable to destruction, censorship or suppression through prohibition of the copying of manuscripts. This includes texts which were to become the basis for modern philosophy and science.